2015
DOI: 10.1148/radiol.14140991
|View full text |Cite
|
Sign up to set email alerts
|

Can Structural Joint Damage Measured with MR Imaging Be Used to Predict Knee Replacement in the Following Year?

Abstract: ).q RSNA, 2014 Purpose:To assess whether magnetic resonance (MR) imagingbased cross-sectional measures of structural joint damage can be used to predict knee replacement during the following year. Materials and Methods:Participants were drawn from the Osteoarthritis Initiative, a longitudinal observational study that includes 4796 participants who have knee osteoarthritis or are at risk. The HIPAA-compliant protocol was approved by the institutional review boards of all participating centers, and written in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 30 publications
2
80
2
Order By: Relevance
“…BMLs are strong and independent predictors of knee cartilage loss, especially site-specific cartilage loss [67,68,69••], and progression of knee cartilage lesions [24,28,67,68,[70][71][72]. BMLs also predict total knee replacement over periods of up to 4 years [49,50,[73][74][75]. In some studies, BMLs predicted knee replacements more strongly than other predictors assessed in the same cohort [49,74].…”
Section: Bone Marrow Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…BMLs are strong and independent predictors of knee cartilage loss, especially site-specific cartilage loss [67,68,69••], and progression of knee cartilage lesions [24,28,67,68,[70][71][72]. BMLs also predict total knee replacement over periods of up to 4 years [49,50,[73][74][75]. In some studies, BMLs predicted knee replacements more strongly than other predictors assessed in the same cohort [49,74].…”
Section: Bone Marrow Lesionsmentioning
confidence: 99%
“…Interestingly, associations between synovial inflammation/effusion and cartilage alterations could be the 'chicken or the egg' dilemma in that, although synovial inflammation could lead to cartilage damage [87], the reverse is also possible [87,88]. The presence of MRI-detected effusion or synovitis predicts knee replacement [75]. Data also showed that chondroitin sulphate, a symptomatic slow acting drug for osteoarthritis (SYSADOA) with DMOAD activity, at 6 months in patients concomitantly taking NSAIDs, significantly reduced the synovial membrane thickness (as assessed by MRI without contrast agent [84]) compared to the placebo group, in addition to decreasing cartilage volume loss [53].…”
Section: Effusion and Synovitismentioning
confidence: 99%
See 1 more Smart Citation
“…For each cartilage, bone marrow or meniscus score, the average of all locations' scores was calculated as the determinant variable ( Table 1). The risk [defined as the hazard ratio (HR) of the subsequent KR] was determined to be contributed by all compartmental scores [20]. BLOKS scorings included full thickness and lesion extent scores for the cartilage (femoral, trochlear, tibial and patellar locations), bone marrow (adjacency, percent edema and size of lesions in the mentioned compartments) and meniscus [lateral/medial; tear (anterior/ posterior/body) and extrusion (medially/laterally)].…”
Section: Analysis Planmentioning
confidence: 99%
“…In a recent investigation, Roemer et al utilized the OAI data sets to demonstrate the value of semiquantitative MRI scorings (MRI Osteoarthritis Knee Score: MOAKS; MOAKS shares some of the scoring features present in either BLOKS or WORMS) in the prediction of KR [20]. They included cases and controls that were matched for gender, age group and radiographic Kellgren-Lawrence (KL) score.…”
Section: Introductionmentioning
confidence: 99%